Sistem Internet of Things untuk Pemantauan Suhu Reaktor Biogas secara Real-time - Dewi Oktafian; Tommy Dwi Putra; Hadis Turmudi (P3M Politeknik Negeri Cilacap, 2026)
This study developed an Internet of Things (IoT)-based system for real-time temperature monitoring of a household biogas reactor. Temperature fluctuations during anaerobic fermentation affect methanogenic microorganism activity and reduce biogas yield. The proposed system utilizes an ESP32 microcontroller, DS18B20 waterproof temperature sensor, LCD display, and Blynk application as a cloud-based monitoring platform. The study involved field observation, system design, implementation, and seven-day testing with a one-minute data logging interval. Results showed that the system operated stably without significant connection loss and provided consistent readings within the 31–33 °C mesophilic range, optimal for anaerobic digestion. The DS18B20 sensor achieved an accuracy of ±0.5 °C compared to a reference thermometer. The system enables operators to monitor fermentation conditions in real time via smartphone or local display, allowing faster response to temperature variations. This research demonstrates that IoT implementation is effective for enhancing temperature monitoring efficiency and offers potential for future automated temperature control development to support energy-independent rural communities. This study contributes to the design of a reliable, low-cost IoT monitoring system for household-scale biogas reactors.